Constructive conflict management Asia-Pacific cases (Sage, 1996)
How did environmental groups and a multinational company agree to halt logging operations in a Korean old-growth forest? How did the families of a Muslim woman and a Hindu man resolve a crisis in the couple's relationship? How did the government of China manage a copyright infringement case between a Japanese company and a Chinese business